A randomized controlled trial comparing results of closed reduction and plaster immobilization versus external fixator in unstable fractures of distal radius - Gupta, HK; Singh, MP (Journal of College of Medical Sciences-Nepal, 2012)
To evaluate the functional and radiological outcome of the two different modalities in unstable fracture distal end of radius, and the complications in each group. Study consists of prospective analysis of the cases of unstable fracture of distal end of radius managed by two different methods of treatment in 40 patients and the functional outcome measured by the standardized functional scoring method (Gartland and Werley 1951, Stewart et al. 1984). The radiological outcome of the fracture management as mentioned above measured according to Anatomical scoring method (Stewart et al. 1984). In this study there was no statistical difference between functional and anatomical outcome when treated by either method. There was no poor graded result anatomically or functionally in either group. No serious complication was noted in both the groups. Both the method of treatment produced no significant difference in outcome, functionally and anatomically , but the extra cost of anaesthetic drugs, operation theatre charges, hazards of anaesthesia and the cost of implants can be avoided in cases managed with closed reduction and immobilization in plaster cast. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 20-27 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6737